3D bioprinting for the production of a perfusable vascularized model of a cancer niche - Maggiotto, Federico; Bova, Lorenzo; Micheli, Sara; Pozzer, Camilla; Fusco, Pina; Sgarbossa, Paolo; Billi, Fabrizio; Cimetta, Elisa (Frontiers in Bioengineering and Biotechnology, 2025)
The ever-growing need for improved in vitro models of human tissues to study both healthy and diseased states is advancing the use of techniques such as 3D Bioprinting. We here present our results on the development of a vascularized and perfusable 3D tumor mimic for studies of the early steps of Neuroblastoma metastatic spread. We used a multi-material and sacrificial bioprinting approach to fabricate vascularized 3D cell-laden structures and developed a customized perfusion system enabling maintenance of growth and viability of the constructs for up to 3 weeks. Cell phenotypes and densities in co-culture for both the bulk of the construct and the endothelialization of the vascular channels were optimized to better replicate in vivo conditions and ideally simulate tumor progression. We proved the formation of an endothelium layer lining the vascular channel after 14 days of perfused culture. Cells in the bulk of the construct reflected Neuroblastoma growth and its tendency to recruit endothelial cells contributing to neovascularization. We also collected preliminary evidence of Neuroblastoma cells migration towards the vascular compartment, recapitulating the first stages of metastatic dissemination.